Comparison of the effects of photon versus carbon ion irradiation when combined with chemotherapy in vitro - Schlaich, Fabian; Brons, Stephan; Haberer, Thomas; Debus, Juergen; Combs, Stephanie E.; Weber, Klaus-Josef (Radiation Oncology, 2013)
Background: Characterization of combination effects of chemotherapy drugs with carbon ions in comparison to photons in vitro.Methods: The human colon adenocarcinoma cell line WiDr was tested for combinations with camptothecin, cisplatin, gemcitabine and paclitaxel. In addition three other human tumour cell lines (A549: lung, LN-229: glioblastoma, PANC-1: pancreas) were tested for the combination with camptothecin. Cells were irradiated with photon doses of 2, 4, 6 and 8 Gy or carbon ion doses of 0.5, 1, 2 and 3 Gy. Cell survival was assessed using the clonogenic growth assay. Treatment dependent changes in cell cycle distribution (up to 12 hours post-treatment) were measured by FACS analysis after propidium-iodide staining. Apoptosis was monitored for up to 36 hours post-treatment by Nicoletti-assay (with qualitative verification using DAPI staining).Results: All cell lines exhibited the well-known increase of killing efficacy per unit dose of carbon ion exposure, with relative biological efficiencies at 10% survival (RBE10) ranging from 2.3 to 3.7 for the different cell lines. In combination with chemotherapy additive toxicity was the prevailing effect. Only in combination with gemcitabine or cisplatin (WiDr) or camptothecin (all cell lines) the photon sensitivity was slightly enhanced, whereas purely independent toxicities were found with the carbon ion irradiation, in all cases. Radiation-induced cell cycle changes displayed the generally observed dose-dependent G2-arrest with little effect on S-phase fraction for all cell lines for photons and for carbon ions. Only paclitaxel showed a significant induction of apoptosis in WiDr cell line but independent of the used radiation quality.Conclusions: Combined effects of different chemotherapeutics with photons or with carbon ions do neither display qualitative nor substantial quantitative differences. Small radiosensitizing effects, when observed with photons are decreased with carbon ions. The data support the idea that a radiochemotherapy with common drugs and carbon ion irradiation might be as feasible as respective photon-based protocols. The present data serve as an important radiobiological basis for further combination experiments, as well as clinical studies on combination treatments. © 2013 Schlaich et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Carbon ion radiotherapy; Chemotherapy; Clonogenic survival; Human tumour cells